2005
DOI: 10.1063/1.1872217
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity switching characteristics and reset currents in NiO films

Abstract: Conductivity switching phenomena controlled by external voltages have been investigated for various NiO films deposited by dc reactive sputtering methods. Pt∕NiO∕Pt capacitor structures with top electrodes of different diameters have showed increasing off-state current with the diameter of a top electrode and nearly the same on-state current independent of the diameter. Local conductivity switching behaviors have been observed in a series structure consisting of two Pt∕NiO∕Pt capacitors with different resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(63 citation statements)
references
References 9 publications
3
60
0
Order By: Relevance
“…Seo et al [14,15] have studied that the effect of the nonstoichiometric ratio between the transition metal and oxygen on the switching properties of NiO. It was found that the more the oxygen content is in the forming gas, the more the nickel vacancies that are generated leading to an increase in the current at the high resistance state.…”
Section: Transition Metal Oxide For Rram Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Seo et al [14,15] have studied that the effect of the nonstoichiometric ratio between the transition metal and oxygen on the switching properties of NiO. It was found that the more the oxygen content is in the forming gas, the more the nickel vacancies that are generated leading to an increase in the current at the high resistance state.…”
Section: Transition Metal Oxide For Rram Applicationsmentioning
confidence: 97%
“…In the early stage, the researches of transition metal oxide such as NiO, TiO 2 , HfO 2 , ZrO 2 , and Nb 2 O 5 mainly focused on their high dielectric constant gate oxide application, but it gradually becomes the current issue because of their good electrical properties that are required to reach the requirements of nonvolatile memory [13][14][15][16].…”
Section: Transition Metal Oxide For Rram Applicationsmentioning
confidence: 99%
“…12 This result is in contrast to results reported for ReRAM elements with electrodes formed using shadow masks without dry etching. [13][14][15] Both R IRS and R HRS are inversely proportional to the device area in devices fabricated without dry etching, suggesting that no filament is present in pristine devices. Since, in the etched device, filaments already present in IRS and are connected in parallel, set switching is expected to be completed when one of the filaments completely connects the top and bottom electrodes and therefore short-circuits them.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 98%
“…It could be said that elucidating the memory characteristics of etched devices, in which filaments are introduced on the etching wall of the oxide layer, is more essential than elucidating those of non-etched devices. [13][14][15] In conclusion, L-dependences of resistance in each resistive state and V set distribution were investigated in dry-etched ReRAM devices. Both <V set > and FWHM decreased with increasing L. This result was reproduced by the simulation based on the model where V set is given by the smallest v set of all the filaments contained in the device, as suggested by the L-dependences of R IRS and R HRS .…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…Up to now, this kind of switching behavior has been found in many materials, such as in SrTiO 3 , NiO, Cu x O, TiO 2 , La 1−x Sr x MnO 3 etc., although their working mechanisms may be different due to their unique material systems [2][3][4][5][6][7]. The large resistive ratio of the so-called 'off' state to the 'on 'state is quite favorable because of the need of a high signal-to-noise ratio for this kind of memory devices.…”
Section: Introductionmentioning
confidence: 99%